CONCEPTUAL ANALYSIS AND METHAPHORICAL MEANING OF NATURAL PHENOMENON IN ENGLISH - Ahmedjanova Dilrabo Asatullayevna (Journals Park Publishing, 2023)
This article discusses significant principles of metaphor themes employed in discourse and usage of passages in English on natural catastrophes to represent a natural phenomenon. The main aim is to reveal what ideological perspective is embedded in such a metaphorical conceptualization, with the focus on the examination of the several sample utterances taken from daily newspapers and reading texts within the frame of natural disaster.
Keywords: metaphor, concept, expression, nature, analysis, disasters, analogue.